Penerapan Asas Kehati-hatian Notaris dalam Menjalankan Kewenangannya Berdasarkan UU Jabatan Notaris dan Kode Etik Notaris - Anand, Ghansham; Sudirman, Sudirman; Darmawan, Monica Caecilia; Nugraha, Xavier (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2024)
One of the primary responsibilities of a Notary is to draft authentic notarial documents related to various legal acts, agreements, and determinations. In exercising this authority, a Notary must adhere to the principle of prudence, which is implicitly regulated in the Law on the Office of Notary (Undang-Undang Jabatan Notaris) and the Notary Code of Ethics. However, these regulations need to explicitly define the principle of prudence, creating ambiguity in its application. This article addresses two key research questions: first, how does a Notary implement the principle of prudence in executing their duties as mandated by the Law on the Office of Notary and the Notary Code of Ethics? Second, what indicators can be used to assess this principle’s application in exercising a Notary’s authority? This research adopts a normative legal approach, utilizing statutory, conceptual, and case-based methodologies. The findings of this study are twofold: first, the regulation of the Notary’s principle of prudence is not specifically defined, leaving it as an open norm subject to multiple interpretations. Second, to address these varying interpretations, seven indicators have been identified to evaluate whether a Notary has acted with prudence in carrying out their duties. These indicators should be comprehensively incorporated into the regulations through a Circular issued by the Ministry of Law and Human Rights or through revisions to the Law on the Office of Notary (hard law) and the Notary Code of Conduct (soft law). AbstrakSalah satu kewenangan Notaris adalah membuat akta autentik mengenai semua perbuatan, perjanjian, dan penetapan, dalam menjalankan kewenangan tersebut hendaknya Notaris menerapkan asas kehati-hatian, sebagaimana diatur secara implisit di dalam Undang-Undang Jabatan Notaris dan Kode Etik Notaris. Permasalahannya, kedua peraturan ini tidak menguraikan secara konkret asas kehati-hatian tersebut sehingga perlu dianalisis mengenai penerapannya. Oleh karenanya, rumusan masalah di dalam artikel ini, yaitu pertama, bagaimana penerapan asas kehati-hatian oleh notaris dalam menjalankan kewenangannya sesuai dengan Undang-Undang Jabatan Notaris dan Kode Etik Notaris? Kedua, apa saja indikator yang dapat digunakan untuk mengevaluasi penerapan asas kehati-hatian oleh Notaris dalam menjalankan kewenangannya? Penelitian ini merupakan penelitian hukum normatif dengan menggunakan pendekatan perundang-undangan, konseptual, dan kasus. Adapun hasil dari penelitian ini adalah pertama, karakteristik pengaturan dari asas kehati-hatian notaris tidak diatur secara spesifik atau sifat pengaturannya dapat dikatakan sebagai open norm, sehingga dalam penerapannya terjadi multitafsir. Kedua, untuk mengatasi keberagaman penafsiran maka ada 7 (tujuh) indikator yang dapat menjadi pertimbangan untuk menilai apakah notaris telah menjalankan kewenangannya dengan hati-hati atau tidak. Tujuh indikator tersebut hendaknya diatur secara komprehensif dalam Surat Edaran Kementerian Hukum dan Hak Asasi Manusia, dan penyempurnaan Undang-Undang Jabatan Notaris (hard law), serta Kode Perilaku Notaris (soft law).